TEACHING THE LESS-SKILLED COMPREHENDERS BY USING “THE FAB FOUR” - Andriani, Fenty (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
This study investigates how the “Fab Four” strategy implemented to teach the less-skilled readers in State Institute of Islamic Studies of Ponorogo.  The design of this study is qualitative. Twenty-seven English department students of the third semester are the subjects of the study. The Fab Four strategy is applied by having the lecturer model four comprehension strategies (summarizing, questioning, predicting, and clarifying) through guided group discussions. Using this strategy, improvements have been noted in students reading comprehension. The result of this study indicates that the “Fab Four” is a great strategy to teach the less-skilled comprehenders as they are trained to determine important ideas from a reading text while discussing vocabulary, developing ideas and questions, and summarizing information.